2022
DOI: 10.1101/2022.02.28.482178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loading-Induced Bone Formation is Mediated by Wnt1 Induction in Osteoblast-Lineage Cells

Abstract: Mechanical loading on the skeleton stimulates bone formation. Although the exact mechanism underlying this process remains unknown, a growing body of evidence indicates that the Wnt signaling pathway is necessary for the skeletal response to loading. Recently, we showed that Wnts produced by osteoblast lineage cells mediate the osteo-anabolic response to tibial loading in adult mice. Here, we report that Wnt1 specifically plays a crucial role in mediating the mechano-adaptive response to loading. Independent o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A previous study reported that a reduction in β-catenin expression within chondrocytes resulted in the degeneration of articular cartilage typically seen in osteoarthritis [31]. Furthermore, Wnt1 has been identified as a regulator of both homeostasis and anabolic processes in the bone tissue of adult mice, particularly during bone formation induced by mechanical loading [32].…”
Section: Effect Of Nicotinamide Mononucleotide On Osteogenesis In Mc3...mentioning
confidence: 99%
“…A previous study reported that a reduction in β-catenin expression within chondrocytes resulted in the degeneration of articular cartilage typically seen in osteoarthritis [31]. Furthermore, Wnt1 has been identified as a regulator of both homeostasis and anabolic processes in the bone tissue of adult mice, particularly during bone formation induced by mechanical loading [32].…”
Section: Effect Of Nicotinamide Mononucleotide On Osteogenesis In Mc3...mentioning
confidence: 99%